Rapid investigation of BA.4/BA.5 cases in France - Kouamen, Alain-Claude; Da Cruz, Helena; Hamidouche, Mohamed; Lamy, Anais; Lloyd, Anna; Castro Alvarez, Javier; Roussel, Mathilde; Josset, Laurence; Enouf, Vincent; Felici, Charlotte; Dos Santos, Georges; Schaeffer, Justine; et al. (Frontiers in Public Health, 2022)
Aim: We aimed to describe the characteristics of individuals infected by BA.4 or BA.5 in France in comparison to BA.1, and analyze the factors associated with hospitalization among BA.4 and BA.5 cases. Methods: A standardized questionnaire was used to collect information on confirmed and probable Omicron cases. Hospitalization risk factors among BA.4/BA.5 cases were analyzed using Poisson regression. Variables with a p-value below 0.2 in the univariate analysis and otherwise relevant were included in the multivariable regression model. Results: The median age of the 301 cases investigated was 47 years and 97% of cases were symptomatic. The most common clinical signs were asthenia/fatigue (75.7%), cough (58.3%), fever (58.3%), headache (52.1%) and rhinorrhea (50.7%). Twelve cases were hospitalized, and 27.1% reported risk factors. No admissions to intensive care and no deaths were reported. Vaccination status was available for 292 cases, 20.9% were unvaccinated, 1.4% had received one dose, 38.3% two doses and 39.4% three doses. Cases presenting at least one risk factor were almost seventeen times more likely to be hospitalized than those with no risk factors (aRR = 16.72 [95% CI 2.59-326.86]). Conclusions: Despite the longer duration of and the differences in symptoms and their possible immune escape, BA.4/BA.5 Omicron sub-lineages globally showed no severe clinical presentation. The presence of at least one risk factor for severe disease significantly increased the risk of hospitalization for those infected with BA.4 or BA.5.